A Quantitative Analysis of Female Employment in Senegal - Malta, Vivian (IMF Working Papers; Working Paper ;, 2019)
Female-to-male employment in Senegal increased by 14 percentage points between 2006 and 2011. During the same period years of education of the working age population increased 27 percent for females and 13 percent for males, reducing gender gaps in education. In this paper, we quantitatively investigate the impact of this increase in education on female employment in Senegal. To that end, we build an overlapping generations model that captures barriers that women face over their life-cycle. Our main findings are: (i) the improvement in years of education can explain up to 44 percent of the observed increased in female-to-male employment ratio and (ii) the rest can be explained by a decline in the discrimination against women in the labor market.